Transcripts associated with chronic lung allograft dysfunction in transbronchial biopsies of lung transplants. Issue 4 (16th December 2021) - Parkes, Michael D.; Halloran, Kieran; Hirji, Alim; Pon, Shane; Weinkauf, Justin; Timofte, Irina L.; Snell, Greg I.; Westall, Glen P.; Havlin, Jan; Lischke, Robert; Zajacová, Andrea; Hachem, Ramsey; et al.
Abstract : Transplanted lungs suffer worse outcomes than other organ transplants with many developing chronic lung allograft dysfunction (CLAD), diagnosed by physiologic changes. Histology of transbronchial biopsies (TBB) yields little insight, and the molecular basis of CLAD is not defined. We hypothesized that gene expression in TBBs would reveal the nature of CLAD and distinguish CLAD from changes due simply to time posttransplant. Whole‐genome mRNA profiling was performed with microarrays in 498 prospectively collected TBBs from the INTERLUNG study, 90 diagnosed as CLAD. Time was associated with increased expression of inflammation genes, for example, CD1E and immunoglobulins. After correcting for time, CLAD manifested not as inflammation but as parenchymal response‐to‐wounding, with increased expression of genes such as HIF1A, SERPINE2, and IGF1 that are increased in many injury and disease states and cancers, associated with development, angiogenesis, and epithelial response‐to‐wounding in pathway analysis. Fibrillar collagen genes were increased in CLAD, indicating matrix changes, and normal transcripts were decreased—dedifferentiation. Gene‐based classifiers predicted CLAD with AUC 0.70 (no time‐correction) and 0.87 (time‐corrected). CLAD related gene sets and classifiers were strongly prognostic for graft failure and correlated with CLAD stage. Thus, in TBBs, molecular changes indicate that CLAD primarily reflects severe parenchymal injury‐induced changes and dedifferentiation. Abstract : This study of 498 transbronchial biopsies of lung allografts shows that tissue gene expression profiles reveal distinct changes that can provide diagnostic assessment of chronic lung allograft dysfunction (CLAD) and reveals that CLAD is a severe parenchymal injury process with similarities to progressive disease states in other organs. Greenland and McDyer comments on page 1012 .